Impact on accessibility, heat distortion and process reliability of planned process interruptions in laser beam brazing processes - Janssen Arend; Stamm Marcel; Spangemacher Lars; Buse Hauke; Schüning Thomas (Production Engineering Archives)
The objective to increase the transferred power (“heat”) of heat exchangers, here finned heat exchangers, leads to an increase in the heat transfer surfaces through thinner wall thicknesses and thus higher packing densities. This transfer can be further optimized by choosing materials with high heat transfer coefficients like copper. Various joining processes, such as welding or brazing can be used to complete the heat exchanger components. Laser beam brazing has an outstanding advantage: heat is applied only where it is needed to create bonds. The base material does not melt and the heat-affected zone becomes smaller, reducing the risk of mechanical distortion. Laser beam brazing has a disadvantage in terms of accessibility. In dense situations, the laser beam may fail to reach its target because the brazed joints may be hidden. Such “shadowing” means that the process cannot be carried out in ideal conditions, i.e., in the case of a circumferential seam, a full, uninterrupted circular movement may not be possible at an angle of incidence of 45 degrees. If steeper or flatter angles are chosen to achieve accessibility, this will result in uneven heating of the parts being joined, in this case the fin and the tube. The work presented shows the development of such brazing process. Firstly, it has to be established whether interruption and resumption of the laser brazing process will produce a usable result and further studies on heat distortion and process stability will be carried out to ensure the process is suitable for batch production.